Imunossensor optoeletrônico para detecção de contaminação de escherichia coli na água - Rodrigues, Domingos Marcelus Carias (2017)
This work proposes the study and development of plastic optical fiber (POF) immunosensors for contaminated water identification in less than an hour. Based on the immune response, the POF is functionalized with an antibody to capture bacteria and identify Escherichia coli concentrations in water. The physical principle fundamental for the immunosensor construction is the variation of light modes guided when the fiber is bent. In the bent fiber some modes escape, according to the refractive index of the external medium of the fiber. Thus, the variation of the external refractive index causes the transmitted optical power changes. The accumulation of bacteria in the POF sensing region causes this variation too, identifying E. coli concentrations in the water. An optoelectronic setup using an Arduino platform is developed to provide and interpret the electrical and optical signals involved in this system. Computational modeling was used for optimizing the immunosensor and proposing advances for future researches.